PROTECTION OF THE RIGHTS OF CHILDREN DEPRIVED OF PARENTAL CARE WITH REGARD TO INTERNATIONAL AGREEMENTS ON FAMILY LAW - Yamnenko, Tetiana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: тo investigate the domestic legal framework in the field of protection of the rights of children deprived of parental care, taking into account international agreements. Methods: documentary analysis and synthesis, comparative analysis, objective truth, cognitive-analytical, etc. Results: the most effective mechanisms for solving problematic issues related to the realization of children’s rights are described and revealed. A new way to solve the problem of ensuring the rights of children deprived of parental planning is also proposed. Discussion: the main international documents determining the development of states to protect and ensure the rights of children deprived of parental care are considered. The legal system of protection of the rights of children left without parental care is analyzed. It is established in which spheres of life of a child deprived of a family environment, the most difficulties are formed. In order to address the problematic issues in the field of protection of the rights of children deprived of parental care, Ukraine needs to make appropriate adjustments to the legislation and take measures aimed at stabilizing the economic situation in the country, which is directly related to improving the situation of children. At the same time, the Ukrainian state has already gone from ignoring international documents on children’s rights to the need to implement minimum international standards into national legislation. However, even today Ukrainian policy is based on the principle of protecting the rights of the child, and not on the principle of ensuring the rights of every child. Therefore, we consider it necessary to move away from the concept of "protection of childhood" to guarantees of the realization of the rights of every child, because the child should be a subject of law, not just an object of protection. The issues of creating favorable conditions for the development and family upbringing of children are also very important and relevant, as the future of the country depends on them.